Evaluation of permanent deformation of a new pavement base and subbase containing unbound granular materials, crumb rubber and crushed glass. (1st September 2019) - Saberian, Mohammad; Li, Jie; Setunge, Sujeeva
Abstract: To avoid premature failures in pavement layers, strong aggregates must be selected for pavement constructions that can bear the accumulation of permanent deformations. Otherwise, rutting happens in the pavement layers due to the accumulation of permanent deformations. On the other hand, due to the extensive generation of construction and demolition (C&D) materials around the world, the application of waste materials in civil engineering projects would be considered as an environmentally friendly and cost-effective solution. Although many studies have been performed to examine the performance of the crushed recycle pavement materials, the literature review shows that few studies have been conducted to examine the permanent deformation characteristic of recycled concrete aggregate (RCA) and crushed rock (CR) containing both crumb rubber (R) and crushed glass (CG). In this study, a series of repeated load triaxial (RLT) tests were carried out to evaluate the permanent deformation (i.e. 100000 loading cycles) of RCA and CR incorporating R and CG. The shakedown theory was used to characterize the permanent deformation behaviour of the samples. Also, Werkmeister's criteria were applied to define the shakedown ranges of the samples. The results show that the RCA, RCA +1% R + 5% CG, CR + 1% R + 3% CG and CR + 1% R + 5% CG can be used as base and sub-base material in pavement. Highlights: Four types of construction and demolition waste materials were used in this study. Different percentages of crushed glass were added to the aggregates containing rubber. Permanent deformation tests were performed. The combination of the wastes can be considered for pavement application.